Exploring the acoustic and prosodic features of a lung-function-sensitive repeated-word speech articulation test - Zeng, Biao; Williams, Edgar Mark; Owen, Chelsea; Zhang, Cong; Davies, Shakiela Khanam; Evans, Keira; Preudhomme, Savannah-Rose (Frontiers in Psychology, 2023)
Introduction Speech breathing is a term usually used to refer to the manner in which expired air and lung mechanics are utilized for the production of the airflow necessary for phonation. Neurologically, speech breathing overrides the normal rhythms of alveolar ventilation. Speech breathing is generated using the diaphragm, glottis, and tongue. The glottis is the opening between the vocal folds in the larynx; it is the primary valve between the lungs and the mouth, and by varying its degree of opening, the sound can be varied. The use of voice as an indicator of health has been widely reported. Chronic obstructive pulmonary disease (COPD) is the most common long-term respiratory disease. The main symptoms of COPD are increasing breathlessness, a persistent chesty cough with phlegm, frequent chest infections, and persistent wheezing. There is no cure for COPD, and it is one of the leading causes of death worldwide. The principal cause of COPD is tobacco smoking, and estimates indicate that COPD will become the third leading cause of death worldwide by 2030. The long-term aim of this research program is to understand how speech generation, breathing, and lung function are linked in people with chronic respiratory diseases such as COPD. Methods This pilot study was designed to test an articulatory speech task that uses a single word (“helicopter”), repeated multiple times, to challenge speech-generated breathing and breathlessness. Specifically, a single-word articulation task was used to challenge respiratory system endurance in people with healthy lungs by asking participants to rapidly repeat the word “helicopter” for three 20-s runs interspersed with two 20-s rest periods of silent relaxed breathing. Acoustic and prosodic features were then extracted from the audio recordings of each adult participant. Results and discussion The pause ratio increased from the first run to the third, representing an increasing demand for breath. These data show that the repeated articulation task challenges speech articulation in a quantifiable manner, which may prove useful in defining respiratory ill-health.